Family presence during resuscitation in paediatric and neonatal cardiac arrest: A systematic review. (May 2021) - Dainty, Katie N.; Atkins, Dianne L.; Breckwoldt, Jan; Maconochie, Ian; Schexnayder, Steve M.; Skrifvars, Markus B.; Tijssen, Janice; Wyllie, Jonathan; Furuta, Marie; Aickin, Richard; Acworth, Jason; Atkins, Dianne; et al.
Abstract: Context: Parent/family presence at pediatric resuscitations has been slow to become consistent practice in hospital settings and has not been universally implemented. A systematic review of the literature on family presence during pediatric and neonatal resuscitation has not been previously conducted. Objective: To conduct a systematic review of the published evidence related to family presence during pediatric and neonatal resuscitation. Data sources: Six major bibliographic databases was undertaken with defined search terms and including literature up to June 14, 2020. Study selection: 3200 titles were retrieved in the initial search; 36 ultimately included for review. Data extraction: Data was double extracted independently by two reviewers and confirmed with the review team. All eligible studies were either survey or interview-based and as such we turned to narrative systematic review methodology. Results: The authors identified two key sets of findings: first, parents/family members want to be offered the option to be present for their child's resuscitation. Secondly, health care provider attitudes varied widely (ranging from 15% to >85%), however, support for family presence increased with previous experience and level of seniority. Limitations: English language only; lack of randomized control trials; quality of the publications. Conclusions: Parents wish to be offered the opportunity to be present but opinions and perspectives on the family presence vary greatly among health care providers. This topic urgently needs high quality, comparative research to measure the actual impact of family presence on patient, family and staff outcomes. PROSPERO registration number: CRD42020140363.